Morphology and Optical Properties of Electropolished Steel in Presence of Vitamin C - Abouzeid, Fatma M. (Asian Journal of Chemistry, 2015)
The studies of steel electrochemical polishing in orthophoshoric acid were performed by potentiodynamic polarization. Electropolishing was conducted in solution containing vitamin C. Addition of vitamin C to electropolishing solution results in a lower limiting current. The concentration of vitamin C influences on electropolishing process and surface texture (AFM, SEM) and UV-VIS-NIR spectroscopy was established. The results show that by increasing vitamin C concentration from 2 × 10-5 to 5 × 10-5 M, roughness and reflectance of steel specimens decrease/increase respectively. The opposite trend is seen when the concentration increases to 10 × 10-5 M. The roughness of steel specimen before electropolishing is 236.7 nm and it will decrease to 140 nm by electropolishing in the presence of 5 × 10-5 M vitamin C. A similar trend is also seen in reflection. The SEM study confirms that low and moderate concentration of vitamin C was effective to enhance levelling and brightness more than higher concentrations.